Kedudukan Hukum Notaris, Akta Notaris Dan Saksi Akta Sebagai Alat Bukti Perkara Perdata (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2002)
Civil law cases of tort lawsuits for an agreement set forth in the form of a notarial deed still dominate the amount recorded in the clerkship of the district court. The notarial deed is one of the written evidence for the parties given and shown at the time of the evidentiary hearing in the district court. The evidence required other than the notarial deed on the agenda of the evidentiary hearing is that the party who filed the tort lawsuit must present a minimum of 2 (two) witnesses. Usually, the witnesses on the notarial deed are 2 (two) employees of the notary office itself. In the practice of trial in the district court, often the notary and 2 (two) witnesses of the deed are not present so that the judge will assess and consider and conclude legally that the plaintiff cannot prove his suit. In general with such an event as mentioned above the judge will make a ruling that the verdict is inadmissible or NO (Niet Ontvankelijk). In an effort to find the answer to the problem, the researcher uses the case study research method. The materials that researchers use are primary and secondary legal materials. The purpose of this study is to find out the important role and function of a notary as a public official making authentic deeds as regulated in The Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law of the Republic of Indonesia Number 30 of 2004 concerning the Position of Notary, the role and function of notarial deeds regulated in Article 1 number 7 of Law No.2/2014 jo Law No.30/2004 where notarial deeds are defined as authentic deeds made by Notary, read by the notary and signed by the parties before the notary according to the established form and procedure, the roles and functions of the 2 (two) deed witnesses who are usually employees of the notary's office itself, which regarding witnesses is regulated in Article 186 HIR, Article 185 HIR, Article 1865 of the Criminal Code and and Article 1866 of the Penal Code which in essence the witness party in a legal event is indispensable as evidence on proof in the event of a civil or criminal dispute and one witness is not a witness (the principle of unus testis nullus testicle). The novelty of this research is in terms of the use of legal theory of civil law evidence and legal theory of civil law proof in analyzing problems. Judging from the legal theory of civil law evidence, a notarial deed is an authentic deed as a perfect proof, meaning that its truth does not require other proofs. Meanwhile, from the aspect of civil law evidentiary legal theory, if the notary and 2 (two) deed witnesses are not present at the evidentiary hearing, the judge does not give an assessment and conclusion that the plaintiff cannot prove his default lawsuit because there is already perfect evidence, namely the notarial deed as an authentic deed. Therefore as a guarantee of legal service, the responsibility of law and moral responsibility should the notary and 2 (two) witnesses of the deed be present and give correct testimony at the evidentiary hearing and the judge does not render an inadmissible judgment or NO (Niet Ontvankelijk). Keywords : civil lawsuit; deed; notary; witness Abstrak Perkara hukum perdata gugatan wanprestasi atas sebuah perjanjian yang dituangkan dalam bentuk akta notaris masih mendominasi jumlahnya yang tercatat di kepaniteraan pengadilan negeri. Akta notaris menjadi salah satu alat bukti tertulis bagi para pihak yang diberikan dan ditunjukkan pada saat agenda sidang pembuktian di pengadilan negeri. Alat bukti yang dibutuhkan selain akta notaris pada agenda sidang pembuktian tersebut adalah adalah pihak yang mengajukan gugatan wanprestasi harus menghadirkan minimal 2 (dua) saksi. Biasanya yang menjadi saksi pada akta notaris adalah 2 (dua) karyawan kantor notaris itu sendiri. Dalam praktek persidangan di pengadilan negeri, seringkali notaris dan 2 (dua) saksi akta tersebut tidak hadir sehingga hakim akan menilai dan mempertimbangkan serta menyimpulkan secara hukum bahwa penggugat tidak bisa membuktikan gugatannya. Pada umumnya dengan kejadian seperti tersebut di atas hakim akan membuat putusan bahwa putusan tidak dapat diterima atau NO (Niet Ontvankelijk). Dalam upaya menemukan jawaban permasalahan, maka peneliti menggunakan metode penelitian studi kasus. Bahan yang peneliti gunakan adalah bahan hukum primer dan sekunder. Tujuan penelitian ini adalah untuk mengetahui peran dan fungsi penting dari seorang notaris sebagai pejabat publik pembuat akta otentik sebagaimana telah diatur diatur dalam Undang-Undang Republik Indonesia Nomor 2 Tahun 2014 tentang Perubahan atas Undang-Undang Republik Indonesia Nomor 30 Tahun 2004 tentang Jabatan Notaris, peran dan fungsi akta notaris yang diatur pada Pasal 1 angka 7 UU No.2/2014 jo UU No.30/2004 yang mana akta notaris didefinisikan sebagai akta otentik yang dibuat oleh Notaris, dibacakan oleh notaris dan ditandatangani oleh para pihak di hadapan notaris menurut bentuk dan tata cara yang ditetapkan, peran dan fungsi 2 (dua) saksi akta yang biasanya adalah merupakan karyawan dari kantor notaris itu sendiri, yang mana mengenai saksi diatur dalam Pasal 186 HIR, Pasal 185 HIR, Pasal 1865 KUHPer dan Pasal 1866 KUHPer yang pada intinya pihak saksi dalam sebuah peristiwa hukum sangat diperlukan sebagai alat bukti pada pembuktian apabila terjadi sengketa secara perdata maupun secara pidana dan satu saksi bukanlah saksi (asas unus testis nullus testis). Kebaruan penelitian ini adalah dalam hal penggunaan teori hukum alat bukti hukum perdata dan teori hukum pembuktian hukum perdata dalam menganalisis permasalahan. Dilihat dari teori hukum alat bukti hukum perdata, maka akta notaris adalah akta otentik sebagai alat bukti yang sempurna artinya kebenarannya tidak memerlukan pembuktian lainnya. Sedangkan dari aspek teori hukum pembuktian hukum perdata, apabila notaris dan 2 (dua) saksi akta tidak hadir pada persidangan pembuktian, hakim tidak memberikan penilaian dan kesimpulan bahwa penggugat tidak bisa membuktikan gugatan wanprestasinya karena sudah ada alat bukti yang sempurna yaitu akta notaris sebagai akta otentik. Oleh karena itu sebagai jaminan pelayanan hukum, tanggung jawab hukum dan tanggung jawab moral hendaknya notaris dan 2 (dua) saksi akta hadir dan memberikan keterangan yang benar di persidangan pembuktian dan hakim tidak memberikan putusan tidak dapat diterima atau NO (Niet Ontvankelijk). Kata Kunci : akta; gugatan perdata; notaris; saksi